The Millenialistic Impulse in European Art and Architecture : Russia and Holland 1913-1922 (GA Document Special Issue)
Se aborda de forma teórica el periodo histórico comprendido entre los años 1913-1922 en Europa y análisis de obras significativas. Contiene: Part 1 The Russian Millenialist Avant-Garde: Constructivist Culture and Eschatological Vision 1913-33. Part 2 Dutch Elementarist Architecture: The De Stijil Movement 1917-31. 1928 J.W.E. Buys & J.B. Lürsen : Cooperative Store, 'Die Volharding' The Hague, Holland. 1928-29 Theo Van Doesburg Hans ARP & Sophie Tauber-ARP : Café L'Aubette Strasbourg, France. 1928-30 Johannes Duiker : Open-air School Cliostraat, Amsterdam, Holland. 1928-30 Mies van der Roeh Tugendthat House Brno, Czechoslovakia. 1928-32 Pierre Chareau Bernard Bijvoet : Maison Dalsace (Maison de Verre) Paris, France. 1929 Mies van der Roeh Lily Reich : German Pavilion, International Exposition, Barcelona, Spain. 1929 Hans Scharoun Hostel Building, Werkbund Exhibition, Breslau, Germany (now Poland). 1929-30 Robert Maillart : Salginatobel Bridge, Near Schiers, Switzerland. 1929-31 Le Corbusier : Villa Savoye, Poissy, France. 1929-32 George Howe William Lescaze : Philadelphia Saving Fund Society Bldg, Philadelphia, Pennsilvania, U.S.A. 1929-33 Alvar Aalto : Paimio Sanatorium, Near Turku, Finland. 1930 William van Allen : Chrysler Building, New York, N.Y., U.S.A.1930-32 E. Owen Williams, in colaboration with Herbert O. Ellis, W.L. Clarke and Robert Atkinson : Daily Express Building, Fleet Street, London, England. 1930-32 Pier Luigi Nervi : Giovanni Berta Stadium, Florence, Italy. 1930-32 E. Owen Williams : Boots Factory, 'Wets' Building, Beeston, Nottingham, England.